O homem e a separação conjugal: aspectos subjetivos de homens após a separação - Vioto, Matheus José (2025)
This study aimed to understand the subjective experiences of heterosexual men aged 25 to 35 following marital separation. A qualitative approach was adopted, involving reflective semi-structured interviews with five participants who met the criteria of age range, sexual orientation, and a minimum interval of one year since the relationship ended. The interviews were analyzed through the lens of analytical psychology, resulting in three themes: the lost war, fallen weapons – soldiers singing about the approaching end; isolated to live, silently to suffer – the futile attempt at overcoming; and warriors with their goddesses to worship – with their disturbed shadows to observe. The results highlighted intense feelings such as despair, anguish, sadness, depression, and loneliness. In many cases, the lack of support networks contributed to destructive behaviors, including alcohol and drug abuse and the pursuit of casual relationships to avoid confronting the pain. One participant stood out for having solid support, commitment to the separation process, and self-care practices. It also became evident that participants took responsibility for their mistakes within the relationship, acknowledging their flaws. The study revealed that traditional models of masculinity hinder the expression of vulnerability, perpetuating silence and suffering. However, when provided with supportive spaces, men showed a willingness to share their experiences, emphasizing the importance of interventions that foster unique and welcoming listening